Consumer Attitude Toward the Issue of Selling Beef Mixed with Boar Meat (Sus sucrofa) and the Intention to Purchase of Meat Consumers in Yogyakarta - Guntoro, B; Burhanuddin, Q; Soeparno, Soeparno (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. This research was aimed to explain the relationship between cognitive, affective and conative combined into the attitude components with the intention to purchase against the issue of mixed beef and boar meatselling in Yogyakarta. The sample of location was at Beringharjo market in which the issues of selling beef and boar meat was established. The research used survey method with interview and questionnaire whose validity and reliability had been proven. The sample of respondents was 80 buyers selected by purposive sampling method. The data were statistically tabulated and analyzed using Chi-square and Phi analyses. The results showed that most of the attitude components i.e. cognitive, affective and conative were classified in favorable category implying that the respondents were responsive and active to look for the information regarding the issue. There was dependent relationship between attitude of the respondents toward the mixed beef and boar meat selling and the intention to purchase it with weak relationship (Phi coefficient of 0.354). It was concluded that consumersâ attitude on the issue of circulation of beefmix with boar meat was to behave more consciously about the truth of the issue and to be worried about the mixed meat.Key Words: consumerâs attitude, purchasing intention, meat consumerAnimal Production 13(3):173-179 (2011)